1994
DOI: 10.1016/s0009-2509(05)80027-2
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic oxidation of organic contaminants in a packed bed reactor

Abstract: Abstract--The catalytic oxidation of several hydrocarbons was studied over noble metal and metal oxide catalysts. A fast empirical method was developed to determine the minimum operating temperature required to guarantee complete conversion of the hydrocarbon.The influence of the operating parameters such as the inlet concentration and residence time, as well as the chemical character of the component to be oxidized, have been investigated. The results can be described satisfactorily by a simple isothermal, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 39 publications
0
10
2
Order By: Relevance
“…As the humidity rises, the conversion declines as the temperature declines. Although several studies 16,22,26 have reported that the presence of water vapor affects conversion, depending upon the catalyst and the temperature, the results herein illustrate that the effects of water vapor markedly inhibit the conversion of LaCoO 3 . This inhibition probably reflected the competition of the CH 2 Cl 2 with water for adsorption on the active sites.…”
Section: Results and Discussion Catalytic Activity Of Lacoo 3 Catalycontrasting
confidence: 49%
See 1 more Smart Citation
“…As the humidity rises, the conversion declines as the temperature declines. Although several studies 16,22,26 have reported that the presence of water vapor affects conversion, depending upon the catalyst and the temperature, the results herein illustrate that the effects of water vapor markedly inhibit the conversion of LaCoO 3 . This inhibition probably reflected the competition of the CH 2 Cl 2 with water for adsorption on the active sites.…”
Section: Results and Discussion Catalytic Activity Of Lacoo 3 Catalycontrasting
confidence: 49%
“…The reduction of the activity might be associated with the competitive adsorption of water vapor and CH 2 Cl 2 at active reaction sites. Although several works 26,30,31 have stated that the presence of water vapor affects the extent of conversion in a manner that depends on the catalyst and the temperature, the results obtained herein indicate that water vapor only weakly suppressed conversion when a LaCoO 3 composite catalyst was used. Thus, increased humidity at the inlet of the gas stream decelerates the conversion of CH 2 Cl 2 over the catalyst.…”
Section: Effects Of Water Vapor On Reactioncontrasting
confidence: 56%
“…The production of tritiated hydrocarbons over the LTR may decrease the overall detritiation performance of the DS. The combustion of hydrocarbons has been extensively reported in the literature [9][10][11]. However, the literature concerning the production of tritiated hydrocarbons over the LTR is limited [12].…”
Section: Introductionmentioning
confidence: 99%
“…The combustion occurs by the reaction of a VOC molecule originating from the gas phase and a catalyst site in an oxidized state. Even if it is criticized by some authors (Vannice [2]), this model proved to be adequate in describing combustion kinetics on the Pt catalyst, even though it emphasizes the presence of the Pt species in the oxidized state on the catalyst surface [3]. However, it is of worth to note that the Mars-van Krevelen and Rideal-Eley rate expressions are formally identical and can be transformed reciprocally by reparameterization [4].…”
Section: Introductionmentioning
confidence: 99%
“…Van de Beld et al [3] investigated the influence of reaction products H 2 O and CO 2 on the ethylene and propane combustion kinetics (individually or in binary mixture) on a Pd/Al 2 O 3 catalyst. Experimental data obtained in this work show that water adsorbs on the surface of the catalyst, introducing a braking effect of the transformation kinetics.…”
Section: Introductionmentioning
confidence: 99%